Teaching the pharyngeal flap and sphincter pharyngoplasty: The sticky note method. Issue 11 (November 2015) - Lee, Jake J.; Jabbour, Noel
Abstract Objective To demonstrate a cost-effective, quick, and easily reproducible three-dimensional sticky note model to enhance the understanding and conceptualization of the geometry and steps of the pharyngeal flap and sphincter pharyngoplasty. Methods The method involves making specified incisions and rearrangements of readily available components, including disposable clear plastic cups, yellow and pink sticky notes, and white paper. Once assembly is complete, further incisions and remodeling are performed to simulate a pharyngeal flap or sphincter pharyngoplasty. Results The cost of the materials to make one model was 0.94. Average construction time was less than 10 min. Conclusion This three-dimensional model is an efficient, interactive, and simple visual aid to teach surgical trainees the geometry and steps of the pharyngeal flap and sphincter pharyngoplasty.